2022
DOI: 10.1093/abt/tbac023
|View full text |Cite
|
Sign up to set email alerts
|

Role of harvest depth filtration in controlling product-related impurities for a bispecific antibody

Abstract: Background Bispecific antibodies (BsAb) belong to a novel antibody category with advantages over traditional mono-specific therapeutic antibodies. However, product variants are also commonly seen during the production of BsAb, which poses significant challenges to downstream processing. In this study, the adsorptive characteristics of a BsAb product and its variants were investigated for a set of depth filters during primary recovery of the cell culture fluid (CCF). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Polymeric binders also play important roles in the charge characteristics of depth filters, however specific information is propriety. A recent study, investigated the properties of D0HC (primary‐cellulose) and X0HC (secondary‐cellulose) for their ability to remove product‐related impurities, specifically low and high‐molecular weight species 27 . They showed that retention of impurities on the primary filter were minimal, due to the open structure and absence of DE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polymeric binders also play important roles in the charge characteristics of depth filters, however specific information is propriety. A recent study, investigated the properties of D0HC (primary‐cellulose) and X0HC (secondary‐cellulose) for their ability to remove product‐related impurities, specifically low and high‐molecular weight species 27 . They showed that retention of impurities on the primary filter were minimal, due to the open structure and absence of DE.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study, investigated the properties of D0HC (primary‐cellulose) and X0HC (secondary‐cellulose) for their ability to remove product‐related impurities, specifically low and high‐molecular weight species. 27 They showed that retention of impurities on the primary filter were minimal, due to the open structure and absence of DE. Retention on the secondary filter was due to a combination of hydrophobic, electrostatic and hydrogen bonding and also dependant on the properties of the target impurity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation